Resources Optimization in ICNs through Distributed Cache Using Software Defined Networking – SDN - Nascimento, Erick B.; de Macedo, Douglas D. J.; Moreno, Edward David (Anais do Simpósio em Sistemas Computacionais de Alto Desempenho (SSCAD); 2018: Anais do XIX Simpósio em Sistemas Computacionais de Alto Desempenho, 2018)
The reduction of the traffic of the network segment by the implementation of caches has been researching object by the exponential increase of data requests through the network. Even though we have high-speed connections, the conventional model still depends on end-to-end communication for established the exchange between two end systems. According to Cisco Virtual Networking Index (VNI), its estimated that by 2021 we will have around 4.6 billion Internet users, with 27.1 billion connected devices and connections. Information Centric Networks (ICN) has been widely discussed as the new content distribution model for the Future of the Internet alongside this the paradigm research of Software Defined Networks (SDN) proposes the flexibility in the development of content networks. Therefore, an architecture for ICN networks orchestrated through SDN is proposed focusing on the use of redundant caching to reduce network degradation caused by the replication of data in the same segment.